2014
DOI: 10.1016/j.bbabio.2014.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of brain-type creatine kinase by AMP-activated protein kinase: Interaction, phosphorylation and ER localization

Abstract: AMP-activated protein kinase (AMPK) and cytosolic brain-type creatine kinase (BCK) cooperate under energy stress to compensate for loss of adenosine triphosphate (ATP) by either stimulating ATP-generating and inhibiting ATP-consuming pathways, or by direct ATP regeneration from phosphocreatine, respectively. Here we report on AMPK-dependent phosphorylation of BCK from different species identified by in vitro screening for AMPK substrates in mouse brain. Mass spectrometry, protein sequencing, and site-directed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 78 publications
1
18
0
Order By: Relevance
“…It consists of at least four distinct spots with same molecular weight but different isoelectric points. The pI shift is typical for phosphorylation events, and indeed BCK autophosphorylation (Hemmer et al 1995) and phosphorylation by protein kinase C (PKC; Chida et al 1990) or AMP-activated protein kinase (AMPK; Ponticos et al 1998;Ramirez Rios et al 2014) have been reported in literature, but was unrelated to mitochondria (Ramirez Rios et al 2014). MS-MS analysis confirmed that all four spots in 2D-PAGE correspond to BCK, but was unable so far to identify a post-translational modification (results not shown).…”
Section: Mitochondriasupporting
confidence: 68%
See 4 more Smart Citations
“…It consists of at least four distinct spots with same molecular weight but different isoelectric points. The pI shift is typical for phosphorylation events, and indeed BCK autophosphorylation (Hemmer et al 1995) and phosphorylation by protein kinase C (PKC; Chida et al 1990) or AMP-activated protein kinase (AMPK; Ponticos et al 1998;Ramirez Rios et al 2014) have been reported in literature, but was unrelated to mitochondria (Ramirez Rios et al 2014). MS-MS analysis confirmed that all four spots in 2D-PAGE correspond to BCK, but was unable so far to identify a post-translational modification (results not shown).…”
Section: Mitochondriasupporting
confidence: 68%
“…Perfused hypoxic transgenic liver with BCK was capable of maintaining global Fig. 4 BCK localization at the ER calcium pump is regulated by phosphorylation via AMPK (Ramirez Rios et al 2014). a BCK from different species in vitro phosphorylated by AMPK.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations